2015
DOI: 10.1159/000374025
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 Inhibits Apoptosis of Pulmonary Endothelial Cells During Acute Lung Injury Through Suppressing SMAD2 Phosphorylation

Abstract: Background/Aims: Angiotensin converting enzyme 2 (ACE2) has an established role in suppressing the severity of acute lung injury (ALI), especially when it was applied together with transplantation of human umbilical cord mesenchymal stem cells (uMSCs). Although the effects of ACE2 in ALI are believed to mainly result from its role in hydrolyzing angiotensin II (AngII), which subsequently reduces the vascular tension and subsequent pulmonary accumulation of inflammatory cells, we and others have recently report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…After acclimatization for 1 week, a group of mice were used as the no-injury group and received no treatments (NT). The lung injury model was induced in another groups of mice, by intraperitoneal administration of the bleomycin solution (10mg/mL, Sigma-Aldrich, St Louis, MO, USA) at 20 mg/kg body weight, as has been applied and described before [6][7][8][9][10]14]. This ALI model is stable and easy to be built.…”
Section: Animal Manipulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…After acclimatization for 1 week, a group of mice were used as the no-injury group and received no treatments (NT). The lung injury model was induced in another groups of mice, by intraperitoneal administration of the bleomycin solution (10mg/mL, Sigma-Aldrich, St Louis, MO, USA) at 20 mg/kg body weight, as has been applied and described before [6][7][8][9][10]14]. This ALI model is stable and easy to be built.…”
Section: Animal Manipulationsmentioning
confidence: 99%
“…Human embryonic kidney 293 cell line (HEK293) and Human lung epithelial cell line HULEC-5a (HULEC) were purchased from ATCC (American Type Culture Collection, Manassas, VA, USA), and has been described before [9]. HULEC-5a is an immortalized human microvascular endothelial cell Line [15], and were maintained in MCDB131 media (without L-Glutamine, ATCC) supplemented with 10ng/ml Epidermal Growth Factor (EGF, Sigma-Aldrich), 1µg/ml Hydrocortisone (Sigma-Aldrich), 10mmol/l Glutamine (Invitrogen, Carlsbad, CA, USA) and 10% fetal bovine serum (FBS, Invitrogen).…”
Section: Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous study has suggested that miR-4262 participates in the development of acute lung injury through regulating the apoptosis of pulmonary endothelial cells (13). Zhang et al (14) and Lu et al (15) have demonstrated that miR-4262 exerts pro-proliferation effect in human cutaneous malignant melanoma cells and hepatocellular carcinoma cells.…”
Section: Introductionmentioning
confidence: 98%